Knowledge and training in paediatric medical traumatic stress and trauma-informed care among emergency medical professionals in low- and middle-income countries - Hoysted, Claire (Eur J Psychotraumatol, 2018)
Background: Provision of psychosocial care, in particular trauma-informed care, in the immediate aftermath of paediatric injury is a recommended strategy to minimize the risk of paediatric medical traumatic stress. Objective: To examine the knowledge of paediatric medical traumatic stress and perspectives on providing trauma-informed care among emergency staff working in low- and middle-income countries (LMICs). Method: Training status, knowledge of paediatric medical traumatic stress, attitudes towards incorporating psychosocial care and barriers experienced were assessed using an online self-report questionnaire. Respondents included 320 emergency staff from 58 LMICs. Data analyses included descriptive statistics, t-tests and multiple regression. Results: Participating emergency staff working in LMICs had a low level of knowledge of paediatric medical traumatic stress. Ninety-one percent of respondents had not received any training or education in paediatric medical traumatic stress, or trauma-informed care for injured children, while 94% of respondents indicated they wanted training in this area. Conclusions: There appears to be a need for training and education of emergency staff in LMICs regarding paediatric medical traumatic stress and trauma-informed care, in particular among staff working in comparatively lower income countries.